How avoiding overreaction to public information? Some insights on central bank communication practices - Emna Trabelsi (Economics and Econometrics Research Institute (EERI), 2012)
It is argued in literature that transparency may be detrimental to welfare. Morris and Shin (2002) suggest reducing the precision of public information or withholding it. The latter seems to be unrealistic. Thus, the issue is not whether central bank should disclose or not its information, but how the central bank should disclose it. We consider a static coordination game in which the private sector receives n semi-public information plus their specific information, and we analyse the impact on the private sector's welfare. The paper consists of three parts: (1) By making assumption that no costs are attached to the provision of private information, we determined the conditions under which the central bank faces a trade-o_ between enhancing commonality and the use of more precise, but fragmented information. Such intermediate transparent strategies may prevent the bad side of public information from overpowering the good side of it. (2) The latter result is found even in presence of positive externalities. (3) Introducing costs to that framework in equilibrium shows that strategic substitutability between semi-public and private precisions is a very likely outcome.
Keywords: D82; D83; E58; 330; Transparency; Central bank Communication; semi public information; private information; static coordination game